2019
DOI: 10.1177/0300985819852132
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic Large T-Cell Lymphoma in the Intestine of Dogs

Abstract: Anaplastic large T-cell lymphoma (ALTCL) is a rare subtype of non-Hodgkin T-cell lymphoma that occasionally occurs in the gastrointestinal tract of humans. Enteropathy-associated T-cell lymphoma (EATL) type 1 is the most common type of intestinal lymphoma in dogs, and ALTCL has not previously been reported in the intestinal tract of dogs. Thirteen dogs with intestinal masses diagnosed as intestinal lymphoma with anaplastic morphology were reviewed. Clinical data, including treatment protocols, were available f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
6
0
1
Order By: Relevance
“…ALCL is a rare type of lymphoma in humans that is characterized by large cells with severe nuclear pleomorphism and CD30 expression. 33 A previous study revealed the expression of CD30 in canine intestinal ALCL 32 ; 3 cases of ALCL expressed CD30. In addition, ALCL showed a significantly higher Ki67 index than eosinophil-dominant mixed inflammatory PTCL and PTCL-NOS.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…ALCL is a rare type of lymphoma in humans that is characterized by large cells with severe nuclear pleomorphism and CD30 expression. 33 A previous study revealed the expression of CD30 in canine intestinal ALCL 32 ; 3 cases of ALCL expressed CD30. In addition, ALCL showed a significantly higher Ki67 index than eosinophil-dominant mixed inflammatory PTCL and PTCL-NOS.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, ALCL showed a significantly higher Ki67 index than eosinophil-dominant mixed inflammatory PTCL and PTCL-NOS. Canine intestinal ALCL is reported to have a poor prognosis with an aggressive clinical course, 32 but information on clinical outcomes was not available in the present study.…”
Section: 9%mentioning
confidence: 86%
“…The latter is classified as a very rare form of human PTCL in the WHO system, but it is discussed separately from PTCL in veterinary medicine because it is common, and clearly distinct from the other types-dogs are older, the disease is indolent and often not treated, and the defining feature of T zone lymphoma is loss of CD45 expression (7, 70), which is not seen in other canine lymphomas. Anaplastic large cell lymphoma (71) and angioimmunoblastic T cell lymphoma (AITL) are diagnosed rarely if at all in dogs (5).…”
Section: Mature T Cell Neoplasms Peripheral T Cell Lymphomamentioning
confidence: 99%
“…Enteropathy-associated T Cell Lymphoma (EATL) is generally investigated via immunohistochemistry and shows positivity to CD3 and occasionally to CD30, a marker of anaplastic lymphoma in humans (40). In rare instances, aberrant co-expression of B cell antigen CD20 is possible (41).…”
Section: Enteropathy-associated T Cell Lymphomamentioning
confidence: 99%